PERBEDAAN SELF EFFIKASI SISWA DITINJAU DARI JENIS KELAMIN PADA SISWA DI MTS DARUL FATIHIN NW GERINTUK KABUPATEN LOMBOK TIMUR - Sukarman Sukarman (JUPE : Jurnal Pendidikan Mandala, 2016)
In Mts darul fatihin NW Gerintuk east Lombok are still many students who do not know the efficacy of self-owned and self-efficacy when asked about there that o not know the answer. students were asked about slf efficacy woman there who do not knowthe answer, but most responded with a smile and shy. While male students who answered firmly and some are answered by not knowing, but less than those of women. It happens to the students of MTs Darul Fatihin NW Gerintuk east Lombok on self-efficacy. Formulationof the problem as follows:”Is there are difference students self-efficacy in terms of gender on students of MTs Darul Fatihin NW Gerintuk east Lombok in academic year 2014/2015?. The aim in this study was to determine the difference students self efficacy in terms of gender on students of MTs Darul Fatihin NW Gerintuk east Lombok in academic year 2014/2015. This study uses a quantitative approach, whit a population of 103 students of MTs Darul Fatihin NW Gerintuk east Lombok in academic year 2014/2015. While the sample in this study amounted to 84 students. Data were collectedby using questionnaires, interview, observation and documentation. Analysis of the data used in this study by using t-test analysis. Based on the results of t-test is 8.06 with a significance level of  5% and db – 82 turned out large numbers rejectionof the null hypothesis that the lim its stated in the t-table is 1,99. This fact suggests that the value of t is greater than t-table (8.06>1.99), this means that the null hypothesis is rejected and the alternative hypothesis is accepted, it can be concluded that: There is difference students self-efficacy in terms of gender on students of MTs Darul Fatihin NW Gerintuk east Lombok in academic year 2014/2015